On Hermite-Hadamard Type Inequalities for s-Convex Functions on the Coordinates via Riemann-Liouville Fractional Integrals - Feixiang Chen (Journal of Applied Mathematics)
We obtain some Hermite-Hadamard type inequalities for s-convex functions on the coordinates via Riemann-Liouville integrals. Some integral inequalities with the right-hand side of the fractional Hermite-Hadamard type inequality are also established.